Análise bibliométrica do controle de pragas de produtos armazenados por óleos essenciais - Santos, Ramon Ferreira dos (Universidade Federal de São Carlos, 2022)
Brazil is one of the biggest producers of grains in the world, but its maximum production potential has been threatened by the presence of stored grain pests that reduce the quality and quantity of grains. Given the inappropriate use of synthetic insecticides, selection pressure makes many of these pests increasingly resistant to control. On the other hand, the growing concern about the health of the population and the environment demands the development of less toxic and persistent products. Thus, essential oils, in their phytocomplexity, have potential for the management of unwanted organisms because they consist of several bioactive compounds, such as terpenes. The aim of this study was a bibliometric analysis of the evolution of the use of essential oils against the main pests of stored products in the world, through a systematic analysis of the bibliography indexed in the Web of Science and Scopus databases, seeking to understand the evolution of production scientific research in the scope of the use of essential oils in the control of pests of stored products, the identification of the main pests according to the analyzed bibliography and also the identification of plant species with potential for use in the control of these insects. Based on this analysis, it was found that the two most frequent species were the beetle Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) and the corn weevil Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae). The data obtained also allowed us to observe the progress of research in the use of these oils in the control of these two pests in the last 20 years, as well as to verify the performance of the main molecules present in oils of species belonging to 39 botanical families in these insects.
Bibliometric analysis of control of stored products pests by essencial oils
Keywords: Coleoptera; Fumigação; Produtos Naturais; Terpenos; Fumigation; Natural Products; Terpenes; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS